2007
DOI: 10.1007/s10508-007-9201-4
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Trading Sex among Homeless Young Adults

Abstract: Although numerous homeless youth report trading sex, few studies have examined risk factors associated with trading sex and even fewer have employed multivariate analyses to examine this relationship, even though trading sex is associated with many negative health outcomes. Based on a sample of 151 homeless young adults in the midwestern United States, logistic regression analyses revealed that for each additional year of age, youth were 37% more likely to have traded sex (AOR = 1.37; 95% CI = .99-1.90). White… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
34
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 30 publications
2
34
0
Order By: Relevance
“…Experiencing more types of partner violence and/or sexual victimization was associated with engaging in a greater number of different HIV risk behaviors. We also found an association between child maltreatment and HIV risk behaviors, which is consistent with previous studies [7,8,12]. Specifically, we found several indirect relationships between child abuse and neglect through other forms of victimization.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Experiencing more types of partner violence and/or sexual victimization was associated with engaging in a greater number of different HIV risk behaviors. We also found an association between child maltreatment and HIV risk behaviors, which is consistent with previous studies [7,8,12]. Specifically, we found several indirect relationships between child abuse and neglect through other forms of victimization.…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, little research exists on partner violence among homeless youth. Although previous studies on homeless young adults have found that child abuse and victimization in general are associated with HIV risk behaviors [7,8,12], it was unknown whether partner violence victimization was a unique and additional risk factor among homeless youth, which our study addresses. We were also able to examine the effects of various forms of victimization on HIV risk behaviors, thus leading to a better understanding of how the circumstances of homeless young people may place them at risk for HIV infection.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Two American studies found similar percentages. Twentyfive percent of the homeless adolescents interviewed (N = 620) claimed to have been involved in prostitution (Yates, Mackenzie, Pennbridge, & Swofford, 1991), while 15% of young adults made the same claim (N = 151) (Tyler, 2009). Some have named this phenomenon''survival sex.…”
Section: Selling Sexmentioning
confidence: 99%